Seleção de ferramentas e caranguejos por macacos-prego (Sapajus libidinosos) em Manguezal - SILVA, Jardeani Mendes da (2019)
In recent years, the study on the use of tools has reached relevance in research related to the evolution of intelligence in primates. Among the neotropical primates, the primates of the Sapajus genus have been distinguished by the habitual use of tools in nature as a way to facilitate access to food resources. The capuchin monkeys use great tools to consume a wide variety of foods. In Brazil, studies on the use of tools on bearded capuchin are mainly aimed at groups living in the cerrado and caatinga. In flooded forests, such as mangroves, records are scarce. In this study, we aimed to verify how Sapajus libidinosus monkeys living in mangroves select tools according to the weight of the crabs and how to use tools in the different age classes of these primates. We assume that heavier crabs are most often consumed with the aid of tools. Assuming that the weight is a variable that correlates positively with the development of the crab and, therefore, with the rigidity of its exoskeleton, it was expected that the use of tools would be more frequent in crabs of greater weight because it presents greater resistance to break. In addition, we anticipate that adults use tools with more frequencies than subadults and juvenile monkeys, because they have greater body weight, more experience and therefore greater capacity and strength for the breaking activity. The research was carried out in the mangroves of the river Preguiças, in the city of Barreirinhas, north coast of Brazil. We carried out an experimental study in a natural environment with the use of wooden feeding platforms fixed to the mangrove roots Rhizophora mangle. The platforms were provisioned with crabs of the species Ucides cordatus along with tools made with wood. The feeding records were obtained from a group represented by 16 animals, in which 8 of them were observed the use of tools. We observed that the animals do not select the tools according to the weight of the crabs, but in relation to the cheliped. The cheliped is probably the most resistant structure of the crab. In addition, we found significant differences between tool weights used by adult monkeys and subadults. This suggests that adults seem to use heavier tools than subadults. However, the use of tools was not observed in young individuals. This study brings new insights into the ecological and evolutionary context of Sapajus libidinosus with the use of tools in mangroves, because unlike what occurs in the caatinga and cerrado, where the tools are stone hammers and used to break fruits, in the mangrove, these animals use mangrove wood tools to access animal food resources like crab.